Collagen as a Biomaterial for Skin and Corneal Wound Healing - Renáta Sklenářová; Naoufal Akla; Meagan Jade Latorre; Jitka Ulrichová; Jana Franková (Journal of Functional Biomaterials, 2022)
The cornea and the skin are two organs that form the outer barrier of the human body. When either is injured (e.g., from surgery, physical trauma, or chemical burns), wound healing is initiated to restore integrity. Many cells are activated during wound healing. In particular, fibroblasts that are stimulated often transition into repair fibroblasts or myofibroblasts that synthesize extracellular matrix (ECM) components into the wound area. Control of wound ECM deposition is critical, as a disorganized ECM can block restoration of function. One of the most abundant structural proteins in the mammalian ECM is collagen. Collagen type I is the main component in connective tissues. It can be readily obtained and purified, and short analogs have also been developed for tissue engineering applications, including modulating the wound healing response. This review discusses the effect of several current collagen implants on the stimulation of corneal and skin wound healing. These range from collagen sponges and hydrogels to films and membranes.